2019
DOI: 10.1007/s00540-019-02715-4
|View full text |Cite
|
Sign up to set email alerts
|

The association of intraoperative end-tidal carbon dioxide with the risk of postoperative nausea and vomiting

Abstract: The number of tables: 2 tablesThe number of figures: 2 figures The supplemental file: 1 figure and 1table

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 18 publications
0
8
0
1
Order By: Relevance
“…Second, due to the sedative and analgesic properties of dexmedetomidine, the amount of intraoperative remifentanil in the experimental group was significantly reduced compared with the control group. However, many studies have reported that remifentanil has a short halflife and quick elimination, and there is no effect on PONV (20)(21)(22). Therefore, although dexmedetomidine reduced the dose of intraoperative remifentanil, it fails to drop the occurrence of PONV.…”
Section: Discussionmentioning
confidence: 99%
“…Second, due to the sedative and analgesic properties of dexmedetomidine, the amount of intraoperative remifentanil in the experimental group was significantly reduced compared with the control group. However, many studies have reported that remifentanil has a short halflife and quick elimination, and there is no effect on PONV (20)(21)(22). Therefore, although dexmedetomidine reduced the dose of intraoperative remifentanil, it fails to drop the occurrence of PONV.…”
Section: Discussionmentioning
confidence: 99%
“…We thank Fujimoto et al for probing the correlation of intraoperative end-tidal carbon dioxide (EtCO 2 ) with the risk of postoperative nausea and vomiting (PONV) in patients undergoing gynecological surgery [1]. We have some comments.…”
Section: To the Editormentioning
confidence: 99%
“…Animal studies have reported that serotonin levels in the brain, a highly emetogenic substance, increase with intestinal 13 , 14 and cerebral ischemia 15 . Based on the hypothesis associating hypocapnia with increased serotonin levels due to intestinal and cerebral ischemia, studies associate intraoperative hypocapnia with increased incidence of PONV 16 , 17 . However, the relationship between hypocapnia and PONV remains unclear because some studies had conflicting results 18 , 19 .…”
Section: Introductionmentioning
confidence: 99%